Bioplastics based on wheat gluten processed by extrusion. (1st December 2019) - Jiménez-Rosado, M.; Zarate-Ramírez, L.S.; Romero, A.; Bengoechea, C.; Partal, P.; Guerrero, A.
Abstract: Recently, bioplastic have generated an increasing interest as an alternative to conventional plastics. For this reason, their manufacture using the traditional techniques used for the production of plastics, such as extrusion, would help transferring bioplastics production to an industrial scale. In this way, the preparation of wheat gluten bioplastics by extrusion was the main objective of this research, modifying their structure by varying the pH value or by incorporating additives (glyoxal or xanthan gum). These bioplastics were characterized by the measurement of their mechanical properties and their water uptake capacity, proving that the modification of bioplastics cause variations in their properties. Thus, extrusion resulted in a greater gluten-plasticizer compatibility compared to compression, as denoted the temperature ramp tests, especially in the presence of additives (ie. Xanthan gum, glyoxal). Moreover, tensile strength was enhanced at pH 9, probably due to bonding promotion at alkaline conditions. These results demonstrate the great potential of these materials for the replacement of conventional plastics. Graphical abstract: Image 1025659 Highlights: Gluten-based extruded materials show promising results for plastic substitution. Extrusion gave rise to a greater compatibility between the bioplastic components. The change of pH improved the water uptake capacity of the bioplastics.